Behavioral profile in a Dctn1G71A knock-in mouse model of Perry disease. (1st November 2021) - Deshimaru, Manami; Mishima, Takayasu; Watanabe, Takuya; Kubota, Kaori; Hosoi, Mana; Kinoshita-Kawada, Mariko; Yuasa-Kawada, Junichi; Ikeda, Maiko; Mori, Masayoshi; Murata, Yusuke; Abe, Takaya; Enjoji, Munechika; et al.
Highlights: Heterozygous Dctn1 G71A mice exhibit depression-like behavior and parkinsonism. TH immunoreactivity in substantia nigral neurons is reduced in Dctn1 G71A mice. Dctn1 G71A mice can be used to study the pathological mechanisms of Perry disease. Abstract: Perry disease (Perry syndrome) is a rare, rapidly progressive, autosomal dominant neurodegenerative disease characterized by parkinsonism, depression/apathy, weight loss, and respiratory symptoms including central hypoventilation. It is caused by missense mutations (e.g. p.G71A) in the DCTN1 gene. We previously generated transgenic mice that expressed human DCTN1 G71A mutant protein under the control of Thy1 promoter. These mice exhibited apathy-like behavior and parkinsonism. However, it is possible that this phenotype was due to a gene-dosage imbalance or transgene insertion position. To circumvent these potential caveats, we have generated a knock-in mouse model carrying a p.G71A mutation in Dctn1 . Heterozygous Dctn1 G71A and wild-type littermates were subjected to a battery of behavioral analyses. Furthermore, immunohistochemistry for tyrosine hydroxylase (TH) was performed on brain sections of these mice, and TH signal intensity in substantia nigral neurons was quantified. Dctn1 G71A mice were immobile for longer than wild-type mice of the same age and sex in the tail-suspension test, revealing depressive characteristics. In addition, the beam-walking test and pole test detected motor deficits in Dctn1 G71A female mice. Finally, immunostaining revealed a decrease in TH immunoreactivity in neurons of the substantia nigra in the Dctn1 G71A mice. Collectively, heterozygous Dctn1 G71A mice showed depression-like behavior, motor deficits, and a functional reduction in substantia nigral neurons, as judged by TH immunostaining, thereby exhibiting multiple features of Perry disease. Hence, this mouse model will be useful in elucidating pathological mechanisms of Perry disease and for developing novel therapeutic strategies against it.